Musculoskeletal screening as a predictor of seasonal injury in elite Olympic class sailors - Schultz, A. B.; Taaffe, D. R.; Blackburn, M.; Logan, P.; White, D.; Drew, M.; Lockie, R. G. (Journal of Science and Medicine in Sport, 2016)
Objectives: To investigate seasonal injury incidence and musculoskeletal screening as a predictor of injury in elite Olympic class sailors. Design: Prospective cohort study. Methods: A 12-month analysis of injury surveillance data was performed for elite Australian sailors (age = 16-30 years, N = 22). Pre-season musculoskeletal screening (incorporating mobility, stability and neural tests) and seasonal injury data were analysed for predictive relationships, and associations between potential predictor variables and injury status. Results: Injuries requiring medical attention occurred at a rate of 3.6 injuries/athlete, while injuries resulting in disability occurred at a rate of 0.6 injuries/athlete, with the lumbar spine the main site of injury (23% and 33%, respectively). Wrist and hand injury resulted in the highest number of days of disability (110 days), followed by injury to the lumbar spine (87 days). Across the season 75% of injuries to the lumbar spine occurred in the latter half of the season. The only screening measure predictive of injured/uninjured status was better left-sided single-leg decline-squat performance (OR = 0.29; 95% CI = 0.09-0.88; p = 0.03), while increasing age was significantly (p = 0.03) associated with thoracic (OR = 1.48; 95% CI = 1.03-2.12) and lumbar spine (OR = 1.46; 95% CI = 1.04-2.04) injury. Conclusions: Though clinically useful, current screening protocols do not adequately assess the risk of seasonal injury in elite Olympic class sailors, and should be revised. Due to the increased risk of spinal injury and potential lost/modified participation in older Olympic class sailors, injury prevention activities should be individualised and age appropriate.